Bridging the Gap Between Manufacturing and Service Through IT-Based Boundary Objects - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (IEEE Transactions on Engineering Management, 2013)
Manufacturing and service companies increasingly engage in networks to provide their customers with integrated solutions. In order to leverage complementary resources and capabilities fully, the network actors must span traditional boundaries between communities of practice in manufacturing and service. Fields like supply chain management and business process management, as well as the literature on boundary spanning, offer little guidance for the systematic identification of boundary objects that could be used to bridge this gap. Drawing on existing works on boundary objects and service blueprinting, we design a new method for diagnosing boundary-spanning processes and identifying candidates for IT-based boundary objects that integrate manufacturing and service companies' subprocesses. The method was iteratively developed over a period of three years in a cyclic action research project with two business-to-business service networks in the mechanical and electrical engineering industries.
Keywords: Service networks; boundary spanning; service blueprinting; business process management; action research